Association between monoallelic TSHR mutations and congenital hypothyroidism: a statistical approach. Issue 2 (February 2018) - Abe, Kiyomi; Narumi, Satoshi; Suwanai, Ayuko S.; Adachi, Masanori; Muroya, Koji; Asakura, Yumi; Nagasaki, Keisuke; Abe, Takayuki; Hasegawa, Tomonobu
Abstract : Objective: Biallelic TSHR mutations cause congenital hypothyroidism (CH). Serum TSH levels of monoallelic mutation carriers range from normal to mildly elevated, and thus the size of its effect remains unclear. The objectives were to examine the association between monoallelic TSHR mutations and positivity at newborn screening (NBS) for CH, and to test whether the association was modified by another genetic factor. Subjects and methods: We enrolled 395 patients that had a positive result in NBS and sequenced TSHR. Monoallelic TSHR mutation carriers were further sequenced for DUOX2 . Molecular functions of the mutations were verified in vitro . The frequency of the mutations in the study subjects was compared with a theoretical value in the Japanese general population. Odds ratio (OR) for NBS positivity associated with the mutation was calculated. Using Bayes' theorem, we estimated a posterior probability of NBS positivity given the mutation. Results: Twenty-six monoallelic TSHR mutation carriers were found. Four out of the 26 also had a monoallelic DUOX2 mutation (double heterozygotes). The frequencies of monoallelic TSHR mutation carriers (6.6%) and double heterozygotes (1.0%) were significantly higher than those in the general population (0.58% and 0.0087%, respectively). OR for NBS positivity of having a monoallelic TSHR mutation or being a double heterozygote was 12.0 or 117.9, respectively. Posterior probability of NBS positivity was 0.38% in monoallelic TSHR mutation carriers and 3.8% in double heterozygotes. Conclusions: Monoallelic TSHR mutations are significantly associated with NBS positivity, and the association is further strengthened by the coexistence of monoallelic DUOX2 mutations.